The Influence of Online Reviews and Online Ratings on Consumer Purchase Decisions of Somethinc Products in Pekanbaru Area with Korean Wave as a Moderating Variable - H, Putri Alisa; Berampu, Lailan Tawila; Taufiqurrahman, Taufiqurrahman (Asian Journal of Management Analytics, 2025)
In Indonesia's growing beauty industry, online reviews and online ratings are critical in shaping consumer purchase decisions. Local beauty brands like Somethinc leverage eWOM to build trust, while the Korean Wave (Hallyu) influences consumer preferences. This study explores the impact of online reviews and online ratings on Somethinc product purchases, with the Korean Wave as a moderating factor. This study designed using a quantitative research design, data was collected via structured questionnaires, and analyzed using Structural Equation Modeling (SEM). The results reveal that online ratings significantly influence purchase decisions, while online reviews show a weaker effect. The Korean Wave moderates the relationship between online ratings and purchase decisions, enhancing their effect, but has a negative moderating effect on online reviews. These results suggest that local beauty brands like Somethinc can benefit from aligning their marketing strategies with global cultural trends, especially those related to Korean beauty standards.